Do Largest Shareholders Incentively Affect Financial Sustainability Under Holdings Heterogeneity? Regulation/Intermediary of Financial Constraints Through Managerial Behavior Games - Zhang, Lipai (Frontiers in Psychology, 2022)
Real estate industry is characterized by a high degree of financial intensity, and is more significant at certain areas. The relative enterprises require certain financial ability and large shareholders’ controlling power to support their survivals and competitiveness. However, due to the multiple adverse impacts of current state policies on banks and private capital, the problem of capital restraints of real estate has become increasingly serious. From corporate governance’s perspective, this paper studies the interactions among financial constraints, ownership concentration and corporate performance under different shareholding states: by analyzing the quantitative characteristics of equity structure, and searching for the appropriate range of the largest shareholder holding ratio, which has considered both the financial sustainability and characteristics. It is found that raising the ownership concentration could enhance supervision effect rather than encroachment, effectively ease the financial constraints and improve the performance of enterprises, both of which are significant under high ownership concentration. Financial constraints play significant intermediary effect in absolute holdings, and have obvious regulatory effects in decentralized equity. Also, the mechanisms of ownership concentration are reflected in the strengthening of corporate supervision, reduced agency costs, improved operating efficiency and increased investment attractiveness. The adjusted behavior add to the responsibility awareness rather than free-ride psychology, forming dynamic game on financial decision. Their financial sustainability in areas would provide nationwide reference for governance reform and managerial behavior.